Finite element modelling of orthogonal cutting: sensitivity analysis of material and contact parameters. (17th October 2012) - Watremez, M.; Méresse, D.; Dubar, L.; Brocail, J.
This paper presents a finite element model of orthogonal cutting developed with Abaqus/explicit software. An Arbitrary Lagrangian-Eulerian (ALE) formulation is used to predict chip formation, temperature, chip-tool contact length, chip thickness, and cutting forces. This numerical model makes possible qualitative analysis of input parameters related to cutting process and frictional models. A sensitivity allows the identification of significant input parameters (coefficients of the Johnson-Cook law, contact and thermal parameters) and their tolerance limits identification. This study draws to input parameters which have to be determined accurately in order to improve numerical approaches of machining.